The Role of Performance-Based Allowances, Work Motivation, and Work Discipline on Employee Performance - Mahmudah, Nji Raden Laila; Pratminingsih, Sri Astuti (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Performance Allowances, Work Motivation, and Work Discipline are essential in improving employee performance. They improve employee abilities and commitment to tasks and affect employee performance. This research aims to find out how Performance Based Allowances, Work Motivation, Work Discipline, and Employee Performance are at the Regional Personnel Agency of the Regional Government of West Java Province, as well as to determine the influence of Performance Based Allowances, Motivation Work, and Work Discipline on Employee Performance. The research method used was descriptive verification analysis with a census/saturated sampling technique. All 137 employees at the Regional Civil Service Agency of the West Java Provincial Government were respondents in this research. Data collection techniques were used by distributing questionnaires to 137 respondents. Calculations were carried out using the Statistical Product and Service Solutions (SPSS) Software Program version 25. The research results show that performance-based allowances, work motivation, and work discipline partially and simultaneously influence employee performance at the Regional Civil Service Agency of the Regional Government of West Java Province.